2018
DOI: 10.5152/turkjsurg.2017.3693
|View full text |Cite
|
Sign up to set email alerts
|

A short term analysis of surgical management of umbilical and paraumbilical hernia

Abstract: Objective: Umbilical hernia and paraumbilical hernia are ventral herniae that occur in infants and adults. According to current evidence, mesh repair is the treatment of choice to avoid recurrence. The aim of this study is to analyze the surgical methods, the types of meshes used, and their benefits. Material and Methods:A retrospective analysis of patients diagnosed with umbilical hernia and paraumbilical hernia was performed. The patients' consent was obtained retrospectively. The various surgical techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
6
1
0
1
Order By: Relevance
“…The mean age of study subjects and female predominance in this study were in line with those reported from previous studies 6,9 . In our study, 39 patients (25.4%) had diabetes mellitus and 46 (30%) patients had hypertension.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The mean age of study subjects and female predominance in this study were in line with those reported from previous studies 6,9 . In our study, 39 patients (25.4%) had diabetes mellitus and 46 (30%) patients had hypertension.…”
Section: Discussionsupporting
confidence: 92%
“…52 (33.9%) patients in this study were obese (BMI≥30) Obesity has been reported at higher rates (67 to 76%) in other studies in the literature 9 . In another study, the mean BMI was reported as 30.4 kg/m 2 in patients who underwent suture-only repair, 36 kg/m 2 in patients who underwent open repair with mesh and 28.9 kg/m 2 in patients who underwent laparoscopic repair with mesh.…”
Section: Discussionsupporting
confidence: 45%
“…The main operative time reported with (group A) was (45.17 min) agree with (Arunagiri, et al [9] study and Elgohary, et al [8] study). Disagree with 4 studies (Ko¨hler, et al [14] study, Sallam, et al [7] study, Elgohary, et al [8] study and Chung, et al [17]…”
Section: Discussionsupporting
confidence: 85%
“…Main age of (group A) was 50.77 years and (group B) was 48.23 years agree with 5 studies (Sallam, et al [7] study, Elgohary, et al [8] study, Arunagiri, et al [9] study, Novitsky, et al [10] study and Cheesborough, et al [11] study). Disagree with 5 studies (Baig, et al [12] study, Nockolds, et al [13] study, Ko¨hler, et al [14] study, Petersson et al [15] study and Wiessner, et al [16] study).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation